2005
DOI: 10.1161/01.cir.0000161799.91577.0a
|View full text |Cite
|
Sign up to set email alerts
|

Body Build and Risk of Cardiovascular Events in Hypertension and Left Ventricular Hypertrophy

Abstract: Background-Obesity may independently increase the risk of adverse events in hypertension with target-organ damage.We investigated whether body build was independently associated with higher cardiovascular risk and whether treatment with losartan relative to atenolol influenced the impact of body build on the primary composite end point of cardiovascular death, stroke, and myocardial infarction and on cardiovascular death in patients with hypertension and left ventricular hypertrophy in the Losartan Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…104,105 Importantly, β-blockers prevented significantly fewer events than these other classes in subgroup analyses restricted to obese subjects. 105,106 The inferiority of β-blockers may relate to several factors, including weight gain (3–4 kg on long-term use), type 2 diabetes, low high-density lipoprotein and high triglycerides. 103,107 β-Blockers also lessen exercise tolerance and cause erectile dysfunction.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…104,105 Importantly, β-blockers prevented significantly fewer events than these other classes in subgroup analyses restricted to obese subjects. 105,106 The inferiority of β-blockers may relate to several factors, including weight gain (3–4 kg on long-term use), type 2 diabetes, low high-density lipoprotein and high triglycerides. 103,107 β-Blockers also lessen exercise tolerance and cause erectile dysfunction.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Four, echocardiographic variables (namely left-ventricular mass) are usually normalized for anthropometric measures to adjust for inter-individual body size variations. The more appropriate method for normalizing left-ventricular mass in adults is still debated: indexation to height 2.7 has been reported to improve LVH detection in obese individuals, whereas indexation to BSA appears more suitable for normal-weight individuals [23,24]. Interestingly, in our study population prevalence of LVH was similar by both indexation methods (2.8 vs. 3.5%).…”
Section: Discussionmentioning
confidence: 51%
“…However, the effect of excessive body weight on CVD in patients with hypertension is less clear [11]. The LIFE (Losartan Intervention for Endpoint reduction in hypertension) study found that higher risks of cardiovascular death were observed in groups with obesity than in normal weight groups [12]. However, a recent study suggested a survival bene t in overweight patients with hypertension compared to subjects with normal weight [13].…”
Section: Introductionmentioning
confidence: 99%